MODERASI BERAGAMA MENURUT PERSPEKTIF TOKOH AGAMA DI KOTA MANADO - Muhammad Tahir Alibe (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2022)
Religious moderation was used as the object of research because they wanted to know the concept of religious moderation of each religious figure based on their respective holy books. This research is a qualitative research, using a love theory approach. it means that the perspectives of various religious figures see other creatures as part of themselves, one family even though they are different. The results of this study indicate that the concept of religious moderation in each religion is essentially based on the concept of compassion for others taught by their respective religions. This means respecting differences in beliefs, differences in how to approach God are not the focus of attention, but it is the basic humanity that causes them to respect each other among fellow creatures. Different humans are a destiny of God but they are like one family so they must love each other, love each other. The conclusion of this study is that Islam, Hinduism, Buddhism, Christianity have the principle of religious moderation based on their respective holy books. Each of their religious teachings teaches to love God's fellow creatures even though they are different, including different religions